Studies on L-asparaginase Activity in Bacillus of Retting Ground - K., Maya; K., Dhevendaran; P., Natarajan (Fishery Technology, 2025)
Cultural conditions for the production of L-asparaginase enzyme by a Bacillus strain isolated from the sediment sample from the retting ground were studied. Two pH optima for enzyme synthesis were observed at 5.6 and 8. The growth was maximum at pH 8. Optimum temperature for this enzyme was at 37Â°C The sodium chloride optima for L-asparaginase production was at 0.2% and for growth at 0.5% concentration. The incorporation of inorganic sulfate even at the minimum concentration inhibited the enzyme activity while inorganic phosphate showed inhibition only at high concentration. Methionine and cysteine enhanced the enzyme activity whereas threonine inhibited the enzyme activity. Sucrose was found to enhance both the activity and growth. Of the four heavy metals, the divalent cation copper at 2 ppm concentration induced the enzyme activity and mercury showed inhibition on growth of bacterium at the same concentration.